Answer:
x = 2
Step-by-step explanation:
8x + 5 = 3x + 15
8x - 3x + 5 = 3x - 3x + 15
5x + 5 = 15
5x + 5 - 5 = 15 - 5
5x = 10
5x / 5 = 10 / 5
x = 2
Answer:
The vertex is (2,1)
Step-by-step explanation:
ƒ(x) = –x^2 + 4x – 3
Factor out the negative
= -(x^2 -4x+3)
Factor
What 2 numbers multiply to +3 and add to -4
-3*-1 = 3
-3+-1 = -4
f(x) = -( x-3)(x-1)
Find the zeros
0 = -( x-3)(x-1)
0 = x-3 0 = x-1
x=3 x=1
The x value of the vertex is 1/2 way between the two zeros
(3+1)/2 = 4/2 =2
To find the y value, substitute x=2 in
f(2) = -( 2-3)(2-1)
=-(-1)(1) = 1
The vertex is (2,1)
Answer:
The answer to your question is:th first option is correct.
Step-by-step explanation:
Here we have and hyperbola with center (0, 1), and the hyperbola is horizontal because x² is positive.
Equation
y - k = ±![\frac{b}{a} (x - h)](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7Ba%7D%20%28x%20-%20h%29)
Process
Find a, b
a² = 9
a = 3
b² = 5
b = √5
h = 0 and k = 1
Substitution
y - 1 = ±![\frac{√5}{3} (x - 0)](https://tex.z-dn.net/?f=%5Cfrac%7B%E2%88%9A5%7D%7B3%7D%20%28x%20-%200%29)
Equation 1
y = ![\frac{\sqrt{5} }{3} x + 1](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B5%7D%20%7D%7B3%7D%20x%20%2B%201)
Equation 2
y = -
6.9
......................................................................
The mean of the data set is 26 because the sum of all the data points divided by the number of data points is 26.4 repeating which rounds to 26.